The factor structure among primary school children of the Strengths and Difficulties Questionnaire of Parents (SDQ-PR) in Malaysia during COVID-19 - Hon Kai Yee; Chua Bee Seok; Crystal Ling (Cogent Social Sciences, 2022)
The Strengths and Difficulties Questionnaire (SDQ) is one of the most widely used questionnaires to measure psychosocial adjustment in children. SDQ has been translated into more than 60 languages. However, a published review of 48 studies from 17 different cultural settings reported that the mean and cut-off scores of the SDQ have shown some variation across cultural settings. The discrepancies found in the existing literatures for the factor structure require further investigation. Thus, the aim of the current study is to evaluate the psychometric properties of parent rating SDQ in the Malaysian context, especially during the pandemic. A total of 315 Malaysian parents of children in the age range of 9 to 11 years old who responded to the online survey participated in this study. The results demonstrated acceptable reliability with the internal consistency of Cronbach’s Alpha ranging from .69 to .79 for the subscales of the SDQ except for the subscale of peer problems (Cronbach’s Alpha = .53) indicated insufficient reliability indexed. The model of SDQ showed a fair fit to the data. The results suggested that peer problem items did not reflect the implication during the pandemic. There is a need to further explore the psychological adjustment after the outbreak of COVID-19.